Transformasi Pelayanan Publik Masjid Jamiâ€™ Nurul Huda melalui Sinergitas Program Smart Surau dan Amal Sosial - Ardiyanto, Yoga Bagas; Putera, Roni Ekha; Aromatica, Desna (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
Padang Panjang City, known as the â€œKota Serambi Mekkahâ€, is determined to become one of the smart cities in West Sumatra. According to Mayor Regulation Number 37 of 2019 concerning the Smart City Masterplan, Padang Panjang City has initiated the smart surau program. The smart surau program aims to restore the pivotal role of surau (mosques) as traditional educational institutions collaborating with internet technology to guide the behavior of adolescents vulnerable to social issues. Masjid Jamiâ€™ Nurul Huda has been chosen as the pilot mosque in Padang Panjang to implement the smart surau program due to its collaboration with Amal Sosial program initiated by the mosque administrators. The research methodology utilized in this study is qualitative descriptive. Data collection techniques encompass direct observation, interviews, documentation, and audiovisual materials. Informant selection is performed using purposive sampling obtained from the interview results. Research findings indicate that the transformation of public services at Masjid Jamiâ€™ Nurul Huda through the smart surau and social welfare programs has a significant impact on meeting the spiritual, social, and religious needs of the surrounding community. Masjid Jamiâ€™ Nurul Huda has successfully adapted to the changing times and taken on a broader role in enhancing quality of life and strengthening social bonds within the community.